Perancangan Antarmuka Pengguna Aplikasi Pengelolaan Program PPK Sekolah menggunakan Metode Human-Centered Design (HCD) (Kasus: SMPI Sabilurrosyad Malang) - Dinda Kanya Anky Putri; Ismiarta Aknuranda; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Penguatan Pendidikan Karakter (PPK) is a national education policy that aims to strengthen the character of students. Through the PPK program, it is hoped that educational units can improve the quality of education, especially in the aspect of building strong character. SMPI Sabilurrosyad is an Islamic junior high school located in the city of Malang, East Java, and is included in the education unit that implements PPK in all school activities. In the past year, SMPI Sabilurrosyad has implemented PPK in the implementation of activities in schools, but the documentation of activities and supporting files is still scattered and not centralized, making it difficult for school to assess the success of the PPK program that has been implemented. With these problems, the researcher designed a web-based application user interface to support the documentation collection process and the PPK program assessment process in schools. The method used is Human Centered Design (HCD) which involves the user at every stage so that the resulting user interface design can meet user needs. This study resulted in two user interface designs in the form of a wireframe and a high-fidelity prototype. The prototypes were evaluated using the Usability Testing technique and the Single Ease Question method to four respondents. The test results obtained indicate that the given task can be done easily by the respondent, but the interface design still needs improvement based on the respondents' suggestions.